2016
DOI: 10.18497/iejee-green.58305
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Affective Constraints on Shaping Environmental Literacy: Model Testing Using Mediator and Moderator Variables

Abstract: The concept of environmental literacy was first defined by Roth in an article for Massachusetts Audebon (1968). He was replying "to the then frequent media references to environmental illiterates who were responsible for polluting the Abstract The aims of this study were; first to investigate the mediating effects of pre-service teachers' (PTs) attitude toward environment on the relationship between their environmental concern and environmental responsibility, and second, to explore the moderating effect of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…The results of Table 11 demonstrate that the direct effect between COVID-19 and O 3 and PM 2.5 concentration is significant, and the indirect impact of COVID-19 is much lower than direct effect in O 3 and PM 2.5 concentration. In other words, the COVID-19 pandemic has a substantial relationship with the concentration of O 3 and PM 2.5 parameters, and the traffic volume has a low effect as the mediator (Hayes 2017 ; Öztürk and Teksöz, 2016 ). Thus, the COVID-19 pandemic has a direct and significant effect on O 3 and PM 2.5 concentration without traffic volume effect because their p value is lower than 0.05.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of Table 11 demonstrate that the direct effect between COVID-19 and O 3 and PM 2.5 concentration is significant, and the indirect impact of COVID-19 is much lower than direct effect in O 3 and PM 2.5 concentration. In other words, the COVID-19 pandemic has a substantial relationship with the concentration of O 3 and PM 2.5 parameters, and the traffic volume has a low effect as the mediator (Hayes 2017 ; Öztürk and Teksöz, 2016 ). Thus, the COVID-19 pandemic has a direct and significant effect on O 3 and PM 2.5 concentration without traffic volume effect because their p value is lower than 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…The moderation and mediation analyses are done based on the Hayes regression procedure (Hayes 2017 ; Öztürk and Teksöz 2016 ). The equation of the analysis is given below: Moderation analysis: Air pollutant concentration ( , and ) = C + C 1*traffic volume + C 2*COVID-19 + C 3*(traffic volume * COVID-19) Mediation analysis: Traffic Volume = i 1 + a * COVID-19 Air pollutant concentration ( , and ) = i 2 + b * traffic volume + c' * COVID-19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Çünkü öğrencilerde bu becerilerin gelişmesi ancak çevresel konularda yeterli ve nitelikli bilgiye, duyarlılığa, farkındalığa, tutuma, sorumluluğa ve bilimsel düşünceye sahip fen bilgisi öğretmenleri sayesinde mümkün olacaktır (Goldman vd., 2017;Keser, 2008;Özden, 2008). Günümüzde ortaya çıkan çevre sorunlarının çözümünün artık ancak bilimsel düşünmeyle ve bilimsel çözüm yöntemleri kullanmayla mümkün olabilecek olması öğretmenlere önemli bir sorumluluk yüklemektedir (Öztürk & Teksöz, 2016;Potter, 2009). Bu ise fen bilgisi öğretmenlerinin, öğretmen adayı oldukları lisans düzeyinde, bahsedilen yeterliklere sahip olarak yetişmelerine bağlıdır (Sadık & Sarı, 2010).…”
Section: Introductionunclassified
“…While some studies (Karpiak & Baril, 2008;Tikka, Kuitunen, & Tynys, 2000) claimed that concerns and favourable relations of females toward environment were better than males, some studies (Katz-Gerro et al, 2015;Koc & Kuvac, 2016;Macdonald & Hara, 1994) indicated that males were more positive attitudes or behaviours toward environmental concerns. Nonetheless, there were some studies claiming that gender did not play significant role in environmentalism (Uyeki & Holland, 2000;Ozturk & Teksoz, 2016).…”
Section: Introductionmentioning
confidence: 99%